Społeczny kontekst edukacji w procesie kształtowania postaw wobec osób niepełnosprawnych = Social context of education in shaping attitudes towards people with disabilities - Banach, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Modern education has many purposes and functions. The transformations occurring in the world naturally generate the need for changes in education system. We pay attention mostly to its influence on development of each and every individual as well as whole society. The thrust of modern education is to optimize human development and its possibilities. The primary objective of this process is to prepare children and youth for prevailing in a given society ideals and goals of education.
Keywords: edukacja; osoby niepełnosprawne; integracja społeczna; education; people with disabilities; social integration